ANALISIS PENGARUH PENGUNGKAPAN SEGMEN OPERASI TERHADAP RISIKO INVESTASI - Handayani, Nenik; Rachmawati, Dyna (Widya Mandala Surabaya Catholic University, 2017)
This study aims to prove empirically the disclosure of operating segments to investment risk. In this study the risk is ex-pected to decrease with the disclosure of operating segment as the basis of investment consideration. The disclosure of operational seg-ments in this study is proxied through quality and quantity, the use of 2 proxies to measure segment disclosure is expected to provide empirical evidence regarding which proxies are more appropriate for measuring disclosure of operating segments. This research uses quantitative design with compound regression hypothesis test. The object of this research is manufacturing company period 2011-2015, with total of 81 observation data. The data used in the form of annual reports of manufacturing companies 2011-2015 period listed in Indonesia Stock Exchange. The results showed that both the quality and the amount of disclosure of the operating segment did not affect the investment risk. This indicates that the quality and number of operating segment disclosures has not been an appropriate proxy for measuring the disclosure of operating segments. The results of this study also shows that firm size has a negative effect on corporate risk, while the level of leverage has a positive effect on investment risk.